Assembly of a Benzo‐Fused Bridged Ketone Scaffold from 1, 5, 10‐Enediynes through One‐Pot Ruthenium‐Catalyzed Cyclization/Iodine‐Mediated Oxidative Ring Expansion. (18th April 2017) - Yamamoto, Yoshihiko; Nishimura, Kei‐ichiro; Mori, Shota; Shibuya, Masatoshi
Abstract: In the presence of a cationic Ru catalyst, 1, 6‐diynes bearing a terminal styryl moiety underwent [2+2+2] cyclization to produce dehydrobiphenylenes fused with a five‐membered ring. Although the cycloadducts were unstable toward purification, their one‐pot iodine‐mediated ring expansion successfully afforded unprecedented bridged ketone products containing a benzo‐fused bicyclo[3.2.1] framework.